Family first : your step-by-step plan for creating a phenomenal family - McGraw, Phillip C., 1950- (New York : Free Press, 2004)
The author examines the crisis in the American family, discussing the importance of the family relationship, its impact on mental health and good child development, and practical, innovative solutions for bringing families back together.
Family matters -- Special strategies for divorced and blended families -- The five factors for a phenomenal family -- your family legacy -- Your parenting style -- Powering up -- Parenting with purpose -- Parenting with clarity -- Parenting by negotiation -- Parenting with currency -- Parenting through change -- Parenting in harmony -- Parenting by example.
Includes bibliographical references (pages 279-286).
Keywords: Parenting; Parent and child; Families; Parent and child; Families; Parent and child; Parenting; Parent and child -- Psychological aspects; Parenting -- Psychological aspects; Parenting; Family; Parents; Family; Child rearing; Interpersonal relations; Social values; Psychological aspects